Soil development within glacier forelands, Southeast Iceland - Olga Kolbrún Vilmundardóttir 1981- (2015)
Glaciers in Iceland have been steadily retreating since the end of the Little Ice Age ~1890, exposing surfaces where weathering and vegetation succession commences. This thesis presents the results from studies on soil development along chronosequences, a time for space substitution, within the fore-fields of Skaftafellsjökull and Breiðamerkurjökull outlet glaciers in SE-Iceland. The study showed that with increasing time since deglaciation and vegetation succession, bulk density and pH (H2O) decreased, while concentrations of loss on ignition (LOI), soil organic carbon (SOC) and total nitrogen (N) along with pH (NaF) increased. There was a slow yet significant increase of ammonium oxalate extractable aluminium (Alox) and iron (Feox) in the oldest moraine at Skaftafellsjökull. Vegetation succession was initially slow but then the vegetation stratigraphy developed in two different directions. Dwarf shrubs and shrubs characterized the oldest moraines at Skaftafellsjökull but grasses at Breiðamerkurjökull where shrubs were completely absent. The rates of soil development were initially slow, reflecting the trend in vegetation succession, but the rates increased after the first 50 years. The highest rates of soil organic carbon accretion (SOC) were reached in the 120 yr-old moraine at Skaftafellsjökull, 9.1 g m-2 yr-1. The rates were considerably lower for Breiðamerkurjökull, reaching 4−4.5 g m-2 yr-1 in the 67−122 yr-old moraines. The rates of increase for both the study sites were considerably lower than compared to sites of revegetation or forestry. Topography affected both vegetation establishment and soil development, where the base of slopes significantly contained higher SOC, N, Alox and Feox concentrations. At Breiðamerkurjökull, avifauna had a point-centered impact on soil formation, creating hot spots within ‘bird hummocks’ on the summits of moraine ridges by adding nutrients through their droppings. The current annual increase in SOC stocks was estimated at 20.7 Mg C yr-1 for Skaftafellsjökull and 19.7 Mg ...